University students' reactions to ChatGPT: Enhancing academic English writing and addressing challenges - Quba, Abdallah Abu; Guba, Mohammed Nour Abu; Awad, Asmaa; Traish, Amira (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates university students' reactions to using ChatGPT to support writing academic English. Data were collected from 200 students across two universities using a survey. Responses showed that most students used the tool regularly, expressing high satisfaction with its contributions to grammar correction, sentence structure improvement, idea generation, and overall coherence. On the other hand, many students reported some challenges, such as misinterpretation of prompts, false information, and lack of personal writing style. Additionally, students overwhelmingly supported integrating ChatGPT into writing classes, emphasizing the need for structured guidance. While ethical concerns about over-reliance and misuse were raised, the majority opposed strict limitations on its use in academic contexts. The study concluded that ChatGPT is a valuable tool that should be integrated into writing curricula with structured guidance and ethical training.